Politicisation of Regional Authorities and Its Impact on the Development of Civil Society in Slovakia - Kancik-Kołtun, Ewelina (Historia i Polityka, 2021)
The paper is an attempt to answer the question to what extent the local government at the regional level in Slovakia is dominated by political parties, and to what extent by independent politicians. The subject of the study are the results of the 2017 local government elections at the regional level and their analysis. The main goal of the paper is to provide a comprehensive, statistical and comparative presentation of the regional election results in Slovakia and show the degree of local authorities’ party-dependency. The secondary objective is to examine how the politicisation of local government influences the development of civil society. An attempt is also made to determine how political competition at the local government level looks like, and whether local entities effectively compete with political parties.